Avaliação do rendimento de grãos de cultivares comerciais de soja com a tecnologia Roundup Ready® para a macrorregião sojícula 1 - Higashi, Wilson Heidi (2011)
This paper aimed at identifying the best cultivars by micro region to be utilized as standard cultivars in the soy improvement program. To do so, thirty one commercial cultivars were evaluated with the tolerance gene to the glyphosate in thirteen environments in 2008/09 crop. Grain yields and cultivar agronomic features such as plant height, lodging and maturity group were evaluated. The trial design used was the randomized block with three repetitions. All the cultural traits were accomplished in order to guarantee the best performance to the environment. This work allowed selecting the cultivars which stood out in grain yields in each micro region. 101 micro region highlighted cultivars: BMX APOLORR, FPS URANORR, FUNDACEP55RR, BMX POTÊNCIARR, BRS 255RR, FUNDACEP53RR, A7636RG, FUNDACEP59RR. 102 micro region cultivars: BMX APOLORR, A6001RG, BMX MAGNARR, V-MAXRR, A7636RG, FUNDACEP53RR and FUNDACEP59RR. 103 micro region cultivars: BMX ENERGIARR, A6411RG, FPS URANORR, FUNDACEP53RR, BMX POTÊNCIARR, A7636RG, FUNDACEP59RR. 104 micro region cultivars: A6411RG, BMX MAGNARR, FPS URANORR, BMX POTÊNCIARR, A7636RG, BRS255RR, TMG4001RR. FUNDACEP59RR